Representation in Design Communication: Meaning-Making in a Collective Context - Phare, Darin M.; Gu, Ning; Ostwald, Michael (Frontiers in Built Environment, 2018)
Drawing on the theory of semiotics, this research measures the differences be-tween a non-expert web crowd and an expert design group, when communicating using varying forms of digital representation in a web-based environment. Using an online tool to capture the interactions in each group, the paper analyses how they independently engage in a design task. In lieu of the crowd’s varying levels of design and disciplinary expertise, semiotics is employed to describe and com-pare how representation is used to conceptualise and express design meaning in both groups. Through this research the paper illustrates that representation is a universally understood object of meaning-making and it demonstrates the capture of design intelligence from the web crowd in terms of its ability to generate de-sign meaning in a collectively shared online space.